2022
DOI: 10.1172/jci160089
|View full text |Cite
|
Sign up to set email alerts
|

Protective α1-antitrypsin effects in autoimmune vasculitis are compromised by methionine oxidation

Abstract: Background. Anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitidies (AAV) are life-threatening systemic autoimmune conditions. ANCA directed against proteinase 3 (PR3) or myeloperoxidase (MPO) bind their cell surfacepresented antigen, activate neutrophils and cause vasculitis. An imbalance between PR3 and its major inhibitor 1-antitrypsin (AAT) was proposed to underlie PR3-but not MPO-AAV. We measured AAT and PR3 in healthies and AAV patients and studied protective AAT effects pertaining to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…145 Interestingly, recent studies showed that a competing peptide and alpha-1 antitrypsin could disrupt the interaction between PR3 and CD177 and that this could inhibit anti-PR3-induced activation, thus highlighting the importance of the PR3-CD177 complex. 99,146 Importantly, we have shown that PR3 can be expressed in the membrane of microvesicles and that these PR3-expressing vesicles could enhance the activity of NADPH oxidase in bystander neutrophils at the site of inflammation to further promote inflammation. 147…”
Section: Mpo and Pr3 As Autoantigensmentioning
confidence: 92%
See 2 more Smart Citations
“…145 Interestingly, recent studies showed that a competing peptide and alpha-1 antitrypsin could disrupt the interaction between PR3 and CD177 and that this could inhibit anti-PR3-induced activation, thus highlighting the importance of the PR3-CD177 complex. 99,146 Importantly, we have shown that PR3 can be expressed in the membrane of microvesicles and that these PR3-expressing vesicles could enhance the activity of NADPH oxidase in bystander neutrophils at the site of inflammation to further promote inflammation. 147…”
Section: Mpo and Pr3 As Autoantigensmentioning
confidence: 92%
“…The association of anti-PR3 ANCA positivity with genes coding for HLA-DP, PR3 itself, and its inhibitor, SERPINA1 (also called alpha-1-antitrypsin) may relate to the levels of target antigen on the neutrophils and the ability of alpha-1 antitrypsin to regulate these levels. 99 In contrast, no direct association with MPO-related genes was found in anti-MPO-associated vasculitis. 100 Recently, the association between risk allele HLA-DPB1*04:01 and PR3-ANCA was further confirmed by functional studies showing that binding between HLA-DPB1*04:01 and PR3 225-239 could initiate an immune response.…”
Section: Ic Vasculitis: a Misdirected Activation Of The Prototypic An...mentioning
confidence: 98%
See 1 more Smart Citation